2007
DOI: 10.1111/j.1467-8284.2007.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic deviance reconsidered

Abstract: non-conductive element having been used in making a connection; or to the connecting link being missing; or to the design being faulty for the purpose.Converting such factors into the Aristotelian four cause classification: efficient, material, formal and final, it is clear that privative causality is not so much a fifth kind of cause, as one of two modes (the other provisive) in which each of the four might operate. Perhaps 'cause' is a yet more extensively analogical notion expressed in the diversity of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…On Schlosser's 12 Similar proposals in defense of nonreductive physicalism in the literature that can be justifiably labeled as "intralevelist" can be found in Crisp and Warfield 2001, Marras 1997, and Yablo 1992. 13 Schlosser defends the CTA in Schlosser 2007Schlosser , 2010aSchlosser , and 2010b The rising interest in the work of Elizabeth Anscombe, especially her seminal work, Intention (1957/2000), has raised doubts in my mind about just how accurate it is to label CTA the "standard story" these days. At the very least, the standard story is becoming less standard among those working in the philosophy of action.…”
Section: Expanding the Supervenience Basementioning
confidence: 91%
“…On Schlosser's 12 Similar proposals in defense of nonreductive physicalism in the literature that can be justifiably labeled as "intralevelist" can be found in Crisp and Warfield 2001, Marras 1997, and Yablo 1992. 13 Schlosser defends the CTA in Schlosser 2007Schlosser , 2010aSchlosser , and 2010b The rising interest in the work of Elizabeth Anscombe, especially her seminal work, Intention (1957/2000), has raised doubts in my mind about just how accurate it is to label CTA the "standard story" these days. At the very least, the standard story is becoming less standard among those working in the philosophy of action.…”
Section: Expanding the Supervenience Basementioning
confidence: 91%
“…5 Some proponents of the causal theory of action, for example, have suggested that beliefs, desires, or intentions constitute an agent's reasons for acting if they cause him to act in a manner that is sensitive to or in virtue of their content (Bishop 1989, chap. 4;Schlosser 2007). Yet, regardless of how one exactly understands such content sensitivity, whether primarily in terms of counterfactual or lawlike correlations, just being told that an agent's behavior is caused by his intention to count the blades of grass in such a context-sensitive manner still does explicate how such an intention can count as a reason for acting or as a consideration speaking in favor of the agent's behavior.…”
Section: Understanding Reasons For Actingmentioning
confidence: 97%
“…The state of nervousness, which connects the intention to the movement, preserves the relation of causation, but it does not preserve the relation of being causally relevant and explanatory in virtue of content. Cases of basic deviance can therefore be excluded by the condition that the rationalizing mental antecedents must be causally efficacious and explanatory in virtue of their intentional contents (Schlosser 2007).…”
Section: Causal Deviance In Actionmentioning
confidence: 99%